3126 Association of ancestral genetic admixture and obesity at 12 months of age - Sahel Hazrati (Journal of Clinical and Translational Science, 2019)
OBJECTIVES/SPECIFIC AIMS: We intended to investigate the relationship between children’s genetic admixture proportions and the incidence of obesity at 12 months of age METHODS/STUDY POPULATION: 821 twelve month old children were included and their genetic admixture was estimated using the ancestry and kinship toolkit (AKT). Weight for Length Percentile (WFLP) at 12 months of age was categorized as <95th percentile and ≥95th percentile. Multiple logistic regression analysis was performed to calculate odds ratios (ORs) with 95% confidence intervals (CIs) for association of admixture proportion including EUR, AMR, AFR, EAS and SAS with WFLP categories adjusting for maternal education, birth weight, frequency of breast feeding and juice consumption RESULTS/ANTICIPATED RESULTS: 821 children were included; WFLP <95th percentile = 671 (81.7%) and WFLP ≥95th percentile = 150 (18.3%). Crude odds ratios showed EUR admixture was protective (OR 0.45 (95% CI 0.27–0.74)) whereas AMR (OR 3.85 (95% CI 1.92 –7.70)) and AFR (OR 5.70 (95% CI 2.19 –14.85)) were positively associated with obesity. After adjusting for confounding variables, only AFR was associated with WFLP≥95th (OR 7.38 (95% CI 2.31 – 23.59)), AMR and EUR were no longer associated with WFLP≥95th DISCUSSION/SIGNIFICANCE OF IMPACT: The AFR admixture proportion remains associated with early childhood obesity after accounting for confounding variables, suggesting the ancestral genetic background may contribute to the differences seen in early childhood obesity